Contrasting functional responses of resident Kupffer cells and recruited liver macrophages to irradiation and liver X receptor stimulation. - Takuya Ishikiriyama (Public Library of Science (PLoS), 2021)
In the murine liver, there are two major macrophage populations, namely resident Kupffer cells (resKCs) with phagocytic activity and recruited macrophages (recMφs) with cytokine-producing capacity. This study was performed to clarify the functional differences between these two populations, focusing on their susceptibility to radiation and response to stimulation via liver X receptors (LXRs), which are implicated in cholesterol metabolism and immune regulation. Liver mononuclear cells (MNCs) were obtained from C57BL/6 (WT) mice with or without 2 Gy irradiation, and the phagocytic activity against Escherichia coli (E. coli) as well as TNF-α production were compared between the two macrophage populations. To assess LXR functions, phagocytosis, TNF-α production, and endocytosis of acetylated low-density lipoprotein (LDL) were compared after synthetic LXR ligand stimulation. Furthermore, LXRα/β knockout (KO) mice and LXRα KO mice were compared with WT mice. Irradiation decreased intracellular TNF-α production by recMφs but did not affect the phagocytic activity of resKCs. In vitro LXR stimulation enhanced E. coli phagocytosis by resKCs but decreased E. coli-stimulated TNF-α production by recMφs. Phagocytic activity and acetylated LDL endocytosis were decreased in both LXRα/β KO mice and LXRα KO mice, with serum TNF-α levels after E. coli injection in the former being higher than those in WT mice. In conclusion, resKCs and recMφs exhibited different functional features in response to radiation and LXR stimulation, highlighting their distinct roles liver immunity and lipid metabolism.